Computational assessment of soot models in ethylene/air laminar diffusion flames - (:unkn) unknown (Taylor & Francis, 2024)
To improve the accuracy of soot formation and evolution predictions, several physical and chemical models have been developed over the last decades. These models include (i) detailed chemical kinetic mechanisms describing both gas-phase chemistry related...
Keywords: Hollín; Llamas de difusión